Hubungan Sikap Asertif dan Konsep Diri Dengan Perilaku Seksual Pranikah Pada Remaja di SMP Negeri 17 Kota Serang - Ike Puspasari Ayu; Nila Marwiyah (Universitas Faletehan, 2019)
Sexual behavior aims to attract the attention of the opposite sex and was related to sexual activity. Sexual behavior in adolescent come from phenomenon of courtship among teenagers which is very common. This research want to know the relationship between assertive behavior and self-concept with premarital sexual behavior adolescents at SMP Negeri 17 Kota Serang. This research was conducted using quantitative methods with a cross sectional approach. The sample in this study was obtained by purposive sampling with a total of 48 students in grade VII and 52 students in grade VIII who were chosen randomly. The result was a relationship between assertive behavior and premarital sexual behavior with p value 0,000 and there was a relationship between self-concept and premarital sexual behavior with p value 0,000. Adolescents must be responsible and firm in maintaining their sexual rights and can make decisions with values ​​​that arise from conscience and not coercion from outside.